Estudo do mecanismo de produção de oligossacarídeos com atividades nutracêuticas a partir da quitosana por hidrólise enzimática com processo fermentativo simultâneo - Pagnoncelli, Maria Giovana Binder (2008)
The obtaining of the oligosaccharides from chitosanase, has showed interest of the pharmaceutical area in the last years due their countless functional properties. Although, the great challenge founded out is how to keep a constant and efficient production. The alternative proposed by this present work was to study the viability to develop an integrated technology, with reduced costs. The strategy used was the obtaining of the oligomers through enzymatic hydrolysis using chitosanolitic enzymes obtained straight from the fermented broth, eliminating this way the phases involved in the enzymes purification. The two chitosanases producing strains chosen for the work, Paenibacillus chitinolyticus and Paenibacillus ehimensis, were evaluated according to the behavior in the culture medium with simple sugar and in relation to the pH medium variations. The culture medium for the chitosanases induction and production was developed through addition of soluble chitosan as carbon source. The soluble chitosan was obtained using hydrochloric acid solution 0.1 M and afterwards neutralization with NaOH 10 M. The enzymatic complexes were obtained from induction process in culture medium with 0.2% of soluble chitosan. The enzymes production was verified soon after the consumption of the simple sugars by the microorganisms and the maximum chitosanolitic activity obtained in the fermented broth by Paenibacillus chitinolyticus was 249 U.L-1 and by Paenibacillus ehimensis was 495U.L-1. These two enzymatic complexes showed stability when stored at 20°C for about 91 days. The enzymes in the fermented broth by Paenibacillus chitinolyticus, when exposed at temperature of 55°C and pH 6.0, where the activity is maximum, showed 50% lost of activity after 3 hours Meanwhile, for the complex produced by Paenibacillus ehimensis, after 6 days of exposure, it was detected 100% of the activity. The chito-oligosaccharides obtained by the hydrolysis of a 1% chitosan solution, using the enzymatic complex produced by Paenibacillus chitinolyticus showed larger quantity after 9 hours hydrolysis and using the complex produced by Paenibacillus ehimensis after 20 minutes was observed the chito-ligosacharides with polymerization degree between 3 and 6 units. Evaluating these results, it was verified that the production of chitosan-oligosaccharides is possible, using a simultaneous process